Nitrogen Contribution by Groundnut (Arachis Hypogaea L.) in a Rotational Cropping System on an Ultisol - Abdul Rahim, Anuar (1991)
In Malaysia, about 120,000 ha of highly weathered Oxisols and Ultisols come off either from rubber or oil palm annually under the replanting programme. Annual crops such as groundnut and maize are often used as cover crops, which can replace non-food legume cover crops, during the first four years under the replanting programme. The acidic nature associated with high aluminum concentration and low native nitrogen status often pose severe constraints to the growth and productivity of annual food crops on these Ultisols. An approach which involved the adoption of advanced legume technology and liming was hypothesized to reduce these two soil-related constraints affecting annual food crop production on Ultisols.